Utilización de una ración suplementaria a base de bagazo de caña enriquecido en la alimentación de vacas holstein en producción en la quinta experimental Punzara de la UNL. - Benítez Ruiz, Carlos Alberto (2019)
This research work was carried out with the purpose of evaluating the productive and economic indicators in crossbred Holstein cows, maintained in grazing, with a supplementary ration based on enriched sugarcane bagasse. The trial lasted 30 days and 12 crossbred Holstein cows were used in production, of different ages, weights and production levels. Each animal constituted an experimental unit, in which two treatments were evaluated in the following way; Treatment one: It consisted of a group of 6 cows in production that were fed only in pasture and served as a control group. It consisted of a group of 6 cows in production that were fed only on grazing and served as a control group. Treatment two: Consisted of a group of 6 cows in production that were kept in pasture plus the supply of 2 kg of supplementary ration based on enriched sugarcane bagasse. The following variables were studied: bromatological analysis of the enriched bagasse and experimental ration of feed consumption, milk production, milk quality, weight change and profitability. The analysis of variance was carried out by means of the design of comparison of means with paired data and the Duncan Test was applied as the test of significance. The results show that the protein enrichment of sugarcane bagasse goes from 1.18% to 11.64%; the average milk production in cows without supplementation is 9.4 liters and cows with supplementation is 9.1 liters, feed consumption in cows without supplementation is 16.5 kg MS/animal/day and cows with supplementation is 15.5 MS/animal/day. Key words: Sugarcane bagasse, supplementary ration, analysis of variance, milk production.